Human colonization of the Arctic the interaction between early migration and the paleoenvironment - Kotli︠a︡kov, V. M. (Vladimir Mikhaĭlovich).; Velichko, A. A. (Andreĭ Alekseevich).; Vasilʹev, S. A. (Sergeĭ Aleksandrovich). (London, United Kingdom Academic Press, 2017)
Human Colonization of the Arctic: The Interaction Between Early Migration and the Paleoenvironment explores the relationship between humans and the environment during this early time of colonization, utilizing analytical methods from both the social and natural sciences to develop a unique, interdisciplinary approach that gives the reader a much broader understanding of the interrelationship between humanity and the environment. As colonization of the polar region was intermittent and irregular, based on how early humans interacted with the land, this book provides a glance into how humans developed new ways to make the region more habitable. The book applies not only to the physical continents, but also the arctic waters. This is how humans succeeded in crossing the Bering Strait and water area between Canadian Arctic Islands. About 4500 years ago , humans reached the northern extremity of Greenland and were able to live through the months of polar nights by both adapting to, and making, changes in their environment.--Provided by publisher.
Postglacial human colonization of Fennoscandia / Paul M. Dolukhanov -- Northern Scandinavia: synthesis / Hans Peter Blankholm, Bryan Hood and Jan Ingolf Kleppe -- Northern Scandinavia : paleogeography of the Kola Peninsula / Tatyana V. Sapelko -- The early Holocene (Mesolithic) sites on the Kola Peninsula / Vladimir Y. Shumkin -- Eastern Fennoscandia and the adjacent regions of the northwestern East European Plain / Paul M. Dolukhanov, Elena A. Kosheleva, Sergey N. Lisitsyn and Dmitriy A. Subetto -- North of the East European Plain / Alexander V. Volokitin and Yuriy N. Gribchenko -- Environments of the northeastern East European Plain at the time of the initial human colonization / Yuriy N. Gribchenko -- Middle and Upper Paleolithic sites in the northeast of the East European Plain / Pavel Yu. Pavlov -- Environments of the Paleolithic sites in the northeast of the East European Plain / Pavel Yu. Pavlov -- Arctic islands of the Barents and Kara seas / Vadim F. Starkov -- West Siberia / Vladimir S. Zykin, Valentina S. Zykina, Sergey V. Markin and Liybov A. Orlova -- North of West Siberia / Evgeniy M. Besprozvanny, Pavel A. Kosintsev and Andrey A. Pogodin -- Central Siberia (the Yenisey-Lana-Yana region) / Yaroslav Y. Kuzmin -- Western Beringia (northeast Asia) / Sergey B. Slobodin, Patricia M. Anderson, Olga Y. Glushkova and Anatoly V. Lozhkin -- Eastern Beringia : climates and environments during the initial peopling / Patricia M. Anderson and Anatoly V. Lozhkin -- The Paleolithic of eastern Beringia from western Alaska to Canadian Yukon / Kelly E. Graf and Ted Goebel -- Peopling of the eastern Canadian Arctic / Julia M. Ross -- First people in Greenland / Jens F. Jensen, Ulla Odgaard, Svend Funder and Patrick Plumet -- Iceland at the time of initial colonization / Olga A. Markelova -- Expansion of ecumene northward and the diet of the Paleolithic population of Eurasia : Neanderthals and Homo sapiens / Mariya V. Dobrovolskaya -- The Mesolithic population in the north of Eastern Europe (reconstruction of social activity according to archaeological and anthropological data) / Alexandra P. Buzhilova -- Way to north : anthropological evidence of adaptivity of the first inhabitants in the high latitudes / Margarita M. Gerasimova -- Genetic data on peopling high latitude areas / Oleg P. Balanovsky -- Stages of the initial human colonization of Arctic and Subarctic / Andrey A. Velichko, Sergey A. Vasilʹev, Yuriy N. Gribchenko and Elena I. Kurenkova.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Human settlements -- History. -- Arctic regions; Paleoecology -- Arctic regions; Human beings -- Migrations; Human ecology -- History. -- Arctic regions; Prehistoric peoples -- Arctic regions; Paleolithic period -- Eurasia; Mesolithic period -- Eurasia; Arctic regions -- Antiquities; Glacial epoch -- Arctic regions; Electronic books